Hubungan Pengetahuan Sikap Dan Perilaku Petugas Terhadap Keterlambatan Klaim Biaya Rawat Inap Peserta Kartu Jakarta Sehat (KJS) di RS Jiwa Dr. Soeharto Heerdjan Tahun 2013 - Siti Nurlaela; Lily Widjaya; Nanda Aula Rumana (Indonesian of Health Information Management Journal (INOHIM), 2015)
Abstract Delay is execution of a job is not in accordance with a predetermined time or not on time. The delay is influenced by various factors. Some of them are knowledge, attitudes and behaviors. Delay claims hospitalization costs resulting cash flow of KJS participants hospital disrupted so would disrupt hospital operations are likely to impact the delivery of health care to patients. The purpose of this study was to determine the relationship of knowledge, attitudes and behavior towards officials delay hospitalization expenses claims KJS participants in RSJ Dr. Soeharto Heerdjan. The method used is quantitative approach to the study of observational and cross-sectional design. The population of this study is related to the implementation of the officer claims hospitalization costs KJS participants are doctors, cashier, Pharmacy, Laboratory, Radiology, Medical Records, and Verification numbering 70 people, while the sample used is saturated sample is the number of the population. Analysis of the data used is univariate and bivariate (chi-square). The results showed that the implementation cost of hospitalization KJS participants claim not timely 52.90%. Knowledge workers on hospitalization expenses claims provisions KJS participants 49.10%. Good officer attitude is 44.30% and good officer behavior is 49.10%. Bivariate test results indicate that there is a significant relationship between knowledge, attitudes and behavior towards hospitalization expenses claims delays KJS participants where P <0.05. The odds ratio for knowledge is 59.813, attitudes 11.429 and behaviors  35.840. Delay claims hospitalization costs KJS participants will result in the timely payment of claims that are not necessary for the implementation of quality improvement officers claim not too late. To improve the knowledge, attitudes and behaviors required personnel training, seminars, socialization, motivation, improved work discipline and responsibility towards work.Keywords : knowledge, attitudes, behavior, and delay claims.AbstrakKeterlambatan adalah pelaksanaan suatu pekerjaan tidak sesuai dengan waktu yang telah ditentukan atau tidak tepat waktu. Keterlambatan dipengaruhi oleh berbagai faktor. Beberapa diantaranya yaitu pengetahuan, sikap dan perilaku. Keterlambatan klaim biaya rawat inap peserta KJS mengakibatkan cash flow rumah sakit terganggu sehingga akan mengganggu operasional rumah sakit yang akan berdampak pula kepada pemberian pelayanan kesehatan kepada pasien. Tujuan penelitian ini untuk mengetahui hubungan pengetahuan, sikap dan perilaku petugas terhadap keterlambatan klaim biaya rawat inap peserta KJS di RS Jiwa Dr. Soeharto Heerdjan. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan observasional serta disain penelitian cross sectional. Populasi penelitian ini adalah petugas yang terkait dengan pelaksanaan klaim biaya rawat inap peserta KJS yaitu dokter, bagian Kasir, Farmasi, Laboratorium, Radiologi, Rekam Medis, dan Verifikasi yang berjumlah 70 orang, sedangkan sampel yang digunakan adalah sampel jenuh yaitu jumlah dari seluruh populasi. Analisa data yang digunakan adalah analisa univariat dan bivariat (chi square). Hasil penelitian menunjukkan bahwa pelaksanaan klaim biaya rawat inap peserta KJS tidak tepat waktu 52,90%. Pengetahuan petugas tentang ketentuan klaim biaya rawat inap peserta KJS 49,10%. Sikap petugas yang baik 44,30% dan perilaku petugas yang baik 49,10%. Hasil uji bivariat menunjukkan bahwa ada hubungan yang bermakna antara pengetahuan, sikap dan perilaku terhadap keterlambatan klaim biaya rawat inap peserta KJS dimana P < 0,05. Odd ratio untuk pengetahuan 59,813, sikap 11,429 dan perilaku 35,840. Keterlambatan klaim biaya rawat inap peserta KJS akan mengakibatkan pembayaran klaim tidak tepat waktu sehingga diperlukan peningkatan kualitas petugas agar pelaksanaan klaim tidak terlambat. Untuk meningkatkan pengetahuan, sikap dan perilaku petugas diperlukan pelatihan, seminar, sosialisasi, pemberian motivasi, peningkatan disiplin kerja dan tanggung jawab terhadap pekerjaan.Kata kunci : Pengetahuan, keterlambatan, klaim.